2002
DOI: 10.1161/01.res.0000043281.66969.32
|View full text |Cite
|
Sign up to set email alerts
|

Fibroblast Growth Factor-2 Gene Transfer Can Stimulate Hepatocyte Growth Factor Expression Irrespective of Hypoxia-Mediated Downregulation in Ischemic Limbs

Abstract: Abstract-Hepatocyte growth factor (HGF) is a potent angiogenic polypeptide that stimulates angiogenesis. Transcriptional regulation of HGF, however, has not been fully defined, with the exception of the hypoxia-mediated downregulation in cultured cells. In the present study, we report that angiogenic growth factors, including HGF, were upregulated in a murine model of critical limb ischemia in vivo, a finding that was in conflict with previous in vitro data. Mice deficient in basic fibroblast growth factor-2 (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
115
2
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(126 citation statements)
references
References 34 publications
8
115
2
1
Order By: Relevance
“…DPPA regulated the differential expression of 4 candidate genes in the array by more than 5‐fold compared to that in the DMSO group (Figure 5A). A report indicated that FGF2 stimulates HGF transcription and protein expression in ischaemic limbs 20. FGF1 and FGF2 are both FGF members that are involved in angiogenesis.…”
Section: Resultsmentioning
confidence: 99%
“…DPPA regulated the differential expression of 4 candidate genes in the array by more than 5‐fold compared to that in the DMSO group (Figure 5A). A report indicated that FGF2 stimulates HGF transcription and protein expression in ischaemic limbs 20. FGF1 and FGF2 are both FGF members that are involved in angiogenesis.…”
Section: Resultsmentioning
confidence: 99%
“…We also confirmed the induction of HIF-1a expression in MRC5 as well as PK8 cells under hypoxia. Together, it is possible that MMP-2, MMP-7, MT1-MMP and cMet in PK8 cells and HGF in MRC5 cells might be upregulated 29,30 Thus it might be noteworthy aspect that HGF secretion from fibroblasts was stimulated under hypoxia. Although we also speculated that the expression of HGF is possibly regulated by HIF-1a.…”
Section: Discussionmentioning
confidence: 99%
“…Le FGF jouerait aussi un rôle de régulateur en amont en stimulant l'expression du VEGF dans les cellules endothéliales et celles du stroma. Dans un modèle de muscle ischémié, in vitro et in vivo, il augmente l'expression du HGF (hepatocyte growth factor) [13]. Dans un autre modèle préclinique de cancer de pancréas, on observe, à la suite de l'administration d'anti-VEGF, un pic de FGF plasmatique qui est associé à une néoangiogenèse secondaire [14,15].…”
Section: Les Inhibiteurs Multispécifiques De Kinase Et Du Complexe Maunclassified